Economics for Humanity: Integrating Well-being, Community, and Practical Philosophy - Mitsuaki Okabe (Routledge, 2025)
Economics is often referred to as ""the queen of social sciences."" This is because mainstream economics has been established as an elegant academic discipline by assuming mankind simply to be homo economicus—an image of human beings showing interest in only material fulfilment and acting solely in his interest. This book challenges this basic perception of human beings. By replacing it with a more realistic and multi-faceted human motive as supported by research in various academic disciplines, the book tries to provide a novel and more plausible picture of human society. Specifically, the book takes in such human aspects as pursuing wellbeing, forming human networks, and the realization of potential of ability. Thus, if we try to better understand human motives and the society, it becomes necessary to replace the conventional two-sector (market-government) social model with a more general and theoretically superior social model, the ""three-sector model"" consisting of market-government-nonprofit sectors. This book demonstrates the validity of this new view by utilizing basic principles of economic policy and social welfare analyses. Moreover, the book has introduced a newly developing practical philosophy in Japan over the last 50 years to achieve both individual wellbeing and better human society.
Keywords: 330; human nature; critique of capitalism; neoclassical economics; heterodox economics; nature of work; meaningful work; wellbeing; humane economics